PERBEDAAN RATA-RATA KEMAMPUAN BERPIKIR MATEMATIS SISWA YANG DIAJARKAN MODEL PEMBELAJARAN PBL BERBANTUAN E-MODUL ETNOLINEAR BERBASIS ETNOMATEMATIKA DENGAN MODEL PEMBELAJARAN LANGSUNG - Kusumawardani Assholihah, Salma Ragil; Sumaji, Sumaji; Rahayu, Ratri (JURNAL MathEdu (Mathematic Education Journal), 2025)
This study aims to determine the difference in the average mathematical thinking ability of students taught by the PBL learning model assisted by an ethnolinear e-module based on ethnomathematics with the direct learning model. The research method used is quantitative, with a quasi-experimental design research form. The study was conducted at SMPN 2 Bae. The population of this study was 246 students. Sampling was carried out using random sampling techniques, namely classes VIII A and VIII D. Data collection techniques with mathematical thinking ability tests. Data analysis techniques using normality tests, homogeneity tests, N-Gain tests, and Mann-Whitney tests. Based on the results of the posttest of mathematical thinking skills, it was found that the average value of the mathematical thinking skills of students in the experimental class who were given treatment using the PBL model assisted by ethnolinear e-modules based on ethnomathematics was 63.71, higher than that of students in the control class who were given treatment using the direct learning model of 46.31, so it can be concluded that the average mathematical thinking skills of students who were taught the PBL learning model assisted by the Ethnolinear e-module were better than those taught the direct learning model.